Age and Gender Segregation of Leishmaniasis Patients in Bukhara Region - J.H.Ozodov; S.O.Sultonov; D. A.Yusupov (Genius Journals, 2022)
Outpatient cards of 1156 patients aged 1 month to 65 years with leishmaniasis from different regions of Bukhara region were retrospectively analyzed. The diagnosis of leishmaniasis was confirmed by clinical, epidemiological, and laboratory methods. Percentage of patients according to age and gender were studied. The incidence of clinical forms of leishmaniasis in young men and women was studied and conclusions were drawn. Based on the obtained results, the indicators were statistically processed. Leishmaniasis has been found to be significantly more common in children aged 5–10 years.
Keywords: Leishmaniasis; Allergic Rhinitis; Bronchial Asthma; Ecology